Life Expectancy With and Without Dementia: A Population-Based Study of Dementia Burden and Preventive Potential. Issue 2 (9th October 2018) - Wolters, Frank J; Tinga, Liselotte M; Dhana, Klodian; Koudstaal, Peter J; Hofman, Albert; Bos, Daniel; Franco, Oscar H; Ikram, M Arfan
Abstract: Reliable population estimates of life expectancy with dementia are required for shaping health-care policy. From the Dutch, population-based Rotterdam Study, 10, 348 persons were followed during 1990-2015 for dementia and death. We created multistate lifetables, and assessed the effect of postponing disease onset. During 120, 673 person-years, 1, 666 persons developed dementia, and 6, 150 died. Overall life expectancy of women ranged from 18.0 years (95% confidence interval (CI): 17.8, 18.2) at age 65 to 2.3 years (95% CI: 2.2, 2.3) at age 95. Of total life expectancy at age 65, 5.7% (1.0 year (95% CI: 1.0, 1.1)) was lived with dementia, increasing with age to 42.1% (1.0 year, 95% CI: 0.9, 1.0) at age 95. For men, life expectancy ranged from 15.6 years (95% CI: 15.4, 15.9) at age 65 to 1.8 years (95% CI: 1.7, 1.8) at age 95, of which 3.7% (95% CI: 0.6 year, 0.5, 0.6) and 35.3% (95% CI: 0.6 year, 0.5, 0.7), respectively, was lived with dementia. Postponing dementia onset by 1–3 years resulted in 25%–57% reductions in years lived with dementia. Survival after diagnosis ranged from 6.7 years (95% CI: 5.3, 8.1) before age 70, to 2.6 years (95% CI: 2.3, 2.9) after age 90. The burden of dementia on individuals and society in terms of healthy life-years lost is large but could potentially be mitigated by preventive interventions at the population level.